Do Firms Hire Politicians as Directors? Evidence from Close Elections - Simon Luechinger; Mark Schelker; Lukas Schmid (CESifo GmbH, 2025)
We document an overrepresentation of politicians on corporate boards using data for Swiss federal legislators in 1931-2015. However, a close-election regression discontinuity design shows that electoral success explains at most a small part of this overrepresentation. We find small and mostly statistically insignificant causal effects on the probability of having at least one directorship and no effect on the number of directorships. Our results imply that the prevalence of politicians on corporate boards stems from a positive selection of talented individuals in both business and politics, rather than firms hiring politicians to gain political access.
Keywords: D72; D73; J45; H11; 330; political connections; politicians; corporate directors; regression discontinuity design